METHODOLOGICAL CHARACTERISTICS OF THE FORMATION OF STUDENTS BASIC COMPETENCES - Jumaniyazova Nodira Khudayberganovna, (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
The article presents pedagogical work experience on the formation of students basic competencies in biology classes.The article demonstrates the ability to combine effective: innovative technologies with traditional, model lessons of various types and structures.